1980
DOI: 10.1159/000260449
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries and the Concentration of Aluminium and Strontium in Enamel

Abstract: The concentration of aluminium and strontium was determined (by AAS) in soil (total and exchangeable), drinking water and dental enamel from an area (Zemunik) with low caries prevalence (DMFT < 2). For comparison purposes, similar samples were collected and analyzed from another village (Novigrad) in the same region with normal caries prevalence (DMFT > 5). A positive correlation between low caries prevalence and a higher concentration of strontium in soil (exchangeable form), drinking water and enamel was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…Steadman et al [1958] found an almost uniform Sr distribution in enamel which was supported by other studies [Vrbic and Stupar, 1980;Noren et al, 1983;Frank et al, 1989], whereas Cutress [1972a] reported either higher surface or higher bulk [Sr] depending on the sample's origin. The concept of a Sr gradient in teeth was also supported by Little and Barrett [1976a,b], who reported higher [Nixon and Helsby, 1976].…”
Section: Sr In Teethsupporting
confidence: 78%
See 3 more Smart Citations
“…Steadman et al [1958] found an almost uniform Sr distribution in enamel which was supported by other studies [Vrbic and Stupar, 1980;Noren et al, 1983;Frank et al, 1989], whereas Cutress [1972a] reported either higher surface or higher bulk [Sr] depending on the sample's origin. The concept of a Sr gradient in teeth was also supported by Little and Barrett [1976a,b], who reported higher [Nixon and Helsby, 1976].…”
Section: Sr In Teethsupporting
confidence: 78%
“…Other elements, such as F, were not studied. A subsequent 13 study by Spector and Curzon [1979] Vrbic and Stupar [1980] were able to demonstrate a negative correlation between [Sr] in enamel and caries incidence, which was supported by athe later studies ofby Athanassouli et al [1983] and Curzon [1985].…”
Section: Epidemiological Caries Studiesmentioning
confidence: 68%
See 2 more Smart Citations
“…Several epidemiologic studies have in dicated an association of strontium (Sr) in drinking water supplies with a lower pre valence of dental caries [Curzon et al, 1978;Vrbic and Stupar, 1980], Although the animal studies have been equivocal, recent reports have shown a tendency for Sr to reduce caries [Ashrafi et al, 1980]. Other studies have shown that the element can readily be incorporated into apatite and bring about changes in lattice parame ters [LeGeroset al, 1978] and to reduce en amel dissolution [Dedhiya et al, 1974].…”
mentioning
confidence: 99%